2019
DOI: 10.6018/analesps.35.2.333101
|View full text |Cite
|
Sign up to set email alerts
|

Dating violence (DV): a systematic meta-analysis review

Abstract: This study summarizes the results of meta-analyses about risk and protective factors related to dating violence (DV). Fifteen studies were included from 1997 to 2018, N = 1784018. The results were classified according to ecological theory. The Zr’s were calculated for each factor and level of analyses, including the differences between victimization and perpetration effect sizes. According to the level of analysis, results showed that the effect sizes were greater for: (1) individual level: cigarette smoking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 62 publications
4
46
1
28
Order By: Relevance
“…Research on traditional dating violence, for instance, has also focused primarily on risk factors for perpetrating physical dating violence, in attempt to understand how to prevent this type of abuse (Peskin et al, 2017). However, analyzing risk factors for victimization is useful for several reasons: i) to promote of a more holistic understanding of the problem, for example, describing the victims' greater psychological vulnerability to the occurrence of abuse (see Hydén, 1995), ii) to determine if the risk factors associated with CDA victimization are similar to those of traditional dating violence and other forms of abuse perpetrated through technologies (e.g., cyberbullying) (Gámez-Guadix et al, 2018); iii) to understand the reciprocity/mutuality of CDA, documented by past evidence (e.g., Leisring & Giumetti, 2014;Morelli et al, 2017;Watkins et al, 2018;Reed et al, 2017), as well as to identify risk factors that increase the likelihood of engaging in both the perpetrator and victim roles; iv) and finally to develop prevention methods aimed at minimizing the consequences of CDA (Gracia-Leiva et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on traditional dating violence, for instance, has also focused primarily on risk factors for perpetrating physical dating violence, in attempt to understand how to prevent this type of abuse (Peskin et al, 2017). However, analyzing risk factors for victimization is useful for several reasons: i) to promote of a more holistic understanding of the problem, for example, describing the victims' greater psychological vulnerability to the occurrence of abuse (see Hydén, 1995), ii) to determine if the risk factors associated with CDA victimization are similar to those of traditional dating violence and other forms of abuse perpetrated through technologies (e.g., cyberbullying) (Gámez-Guadix et al, 2018); iii) to understand the reciprocity/mutuality of CDA, documented by past evidence (e.g., Leisring & Giumetti, 2014;Morelli et al, 2017;Watkins et al, 2018;Reed et al, 2017), as well as to identify risk factors that increase the likelihood of engaging in both the perpetrator and victim roles; iv) and finally to develop prevention methods aimed at minimizing the consequences of CDA (Gracia-Leiva et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Taylor & Xia, 2018). Gracia-Leiva et al (2019), in their metaanalysis on DV, found that the social and community environment was more closely related to DV as opposed to individual factors. It is important to continue exploring these somewhat neglected risk and protective factors of youth CDA in order to determine if they are indeed unrelated to the phenomenon or if our conclusions result from the limited number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…As for age, in relation to perpetration, 75.6% of the sample were adolescents between 15 and 17 years old and 24.4% were between 12 and 14 years old, χ 2 = 7.90, p < 0.01, Cramer's V = 0.17. Likewise, in relation to victimization, 80.4% belonged to the oldest group (15)(16)(17) and 19.6% belonged to the youngest (12)(13)(14), χ 2 = 20.42, p < 0.01, Cramer's V = 0.28. In this case, the associations, although statistically significant, indicated a smaller effect size than that found with sex.…”
Section: The Victimization and Perpetration Of Teen Dating Violence Amentioning
confidence: 98%
“…There are important differences in the prevalence rates of the different EU-28 Member States that may be due to multiple individual, political and socio-cultural factors. A recent meta-analysis on dating violence concludes that factors related to the socio-community environment (for example, belonging to dangerous neighbourhoods) are closely associated with the perpetration of dating violence (Gracia-Leiva, Puente-Martínez, Ubillos-Landa & Páez-Rovira, 2019). Several studies show that there are no significant differences between GV aggressors and other male offenders in terms of the psychopathological characteristics of the offenders Sjödin, Wallinius, Billstedt, Hofvander & Nilsson, 2017) or their educational level (Loinaz, Marzbal & Andrés-Pueyo, 2018).…”
Section: Discussionmentioning
confidence: 99%